Haplotype Block Analysis Reveals Candidate Genes and QTLs for Meat Quality and Disease Resistance in Chinese Jiangquhai Pig Breed - Oyelami, Favour Oluwapelumi; Zhao, Qingbo; Xu, Zhong; Zhang, Zhe; Sun, Hao; Zhang, Zhenyang; Ma, Peipei; Wang, Qishan; Pan, Yuchun (Frontiers in Genetics, 2020)
The Jiangquhai (JQ) pig breed is one of the most widely recognized pig population in China due to its unique and dominant characteristics. In this study, we report the extent of Linkage disequilibrium (LD) and haplotype block structure of the JQ pig breed and scanned the blocks for possible genes underlying important QTLs that could either be responsible for some adaptive features in these pigs or might have undergone some selection pressure. We compared some of our results with other Chinese and Western pig breeds. The results show that the JQ breed had the highest total block length (349.73 Mb≈15% of its genome), and the coverage rate of blocks in most of its chromosomes was larger than those of other breeds except for Sus scrofa chromosome 4 (SSC4), SSC6, SSC7, SSC8, SSC10, SSC12, SSC13, SSC14, SSC17, SSC18, and SSCX. Moreover, the JQ breed had more SNPs that were clustered into haplotype blocks than the other breeds examined in this study. Our shared and unique haplotype block analysis revealed that Hongdenglong(HD) breed had the lowest percentage of shared haplotype blocks while Shanzhu (SZ) breed had the highest. We found that JQ had an average r2>0.2 at SNPs distances 10-20kb and concluded that about 120,000 to 240,000 SNPs would be needed for a successful GWAS in the breed. Finally, we detected a total of 88 genes harboured by selected haplotype blocks in the JQ breed of which only 4 were significantly enriched (p-value≤0.05). These genes were significantly enriched in 2 GO terms (p-value<0.01), and 2 KEGG pathways (p-value<0.02). Most of these enriched genes were related to health. Also, most of the overlapping QTLs detected in the haplotype blocks were related to meat and carcass quality, and health, with a few of them relating to reproduction and production. These results provide insights into the genetic architecture of some adaptive and meat quality traits observed in the JQ pig breed and also revealed the pattern of LD in the genome of the pig. Our result provides significant guidance for improving the statistical power of GWAS and optimizing conservation strategy for this JQ pig breed.